Implementation of the Population Administration Service Improvement Program in Making Electronic ID Cards at the Makassar City Population and Civil Registry Office - Jumniarti; Haedar Akib; Herman H; arti, jumni (Universitas Negeri Makassar, 2026)
This study aims to examine and explain the implementation process of the population administration service improvement program, as well as supporting and inhibiting factors for the implementation of the program in improving population administration services in making Electronic ID Cards at the Population and Civil Registration Service of Makassar City. The type of research is descriptive qualitative. Data collection techniques through observation, interviews and documentation. Data analysis techniques include data condensation, data presentation, and drawing conclusions. In terms of communication, it is good, this can be shown from the wide, consistent, and clear dissemination of information through various media, as well as easy access for the public. Resources are good, this is shown from the availability of technology and competent human resources in supporting e-ID card services efficiently and effectively. Attitudes and commitments are good, this can be shown from the professionalism, discipline, and dedication of officers in providing fast, accurate, and friendly services. The bureaucratic structure is good, shown by the efficiency of service flows and strict supervision in performance evaluations. The organizational environment is good, shown by a dynamic work atmosphere, responsiveness of officers, and solid coordination and cooperation. The size and objective factors are good, shown by systematic implementation, proactive steps, and consistency of implementation according to targets even though there are still technical obstacles. Politics in the implementation of e-KTP in Disdukcapil is good, as shown by the neutrality and professionalism that are maintained, and supported by stable regulations that ensure that e-KTP functions strategically in state administration. Funding is good, as shown by sufficient budget allocation and structured management according to government regulations, although there are still obstacles in the availability of forms due to dependence on central allocations. Recruitment is good, as seen from the suitability of officers to their duties, although without strict selection, still considering service capabilities, with competent officers and supported by training. Supporting factors for the e-KTP program in Dukcapil Makassar City are good, as seen from technological support and compliance with procedures. Meanwhile, inhibiting factors are not optimal, as shown by limited facilities and infrastructure such as stock of forms and internet networks that still hinder services, as well as dependence on the center in procuring forms which often causes delays.